Non-invasive tools to estimate stress-induced changes in photosynthetic performance in plants inhabiting Mediterranean areas - Guidi, Lucia; Calatayud, Angeles (Environmental and Experimental Botany, 2013)
In Mediterranean areas, plants are concomitantly exposed to various abiotic stresses such as light intensity, water deficit, extremes in air temperature, air pollutants, etc. These environmental pressures adversely affect plant development. Changes in photosystem activity are an early response of plants to abiotic stresses. Therefore, chlorophyll (Chl) fluorescence and gas exchange, two non-invasive, rapid and inexpensive techniques for measuring photosynthesis in leaves, have been widely used by plant ecophysiologists to analyse plant responses to stressful conditions. Chl a fluorescence and gas exchange parameters can be indeed used to evaluate changes in photochemical and non-photochemical processes in photosystems associated with electron transport, CO2 fixation, and heat dissipation. In this review, we focus our analysis on the effects of different abiotic stresses on the photochemistry of Mediterranean plants using Chl a fluorescence and gas exchange measurements. Since changes in photosynthetic parameters are observed in the absence of visual injuries, these methodologies constitute fundamental tools to predict and evaluate the extent to which abiotic stresses damage photosynthesis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Abiotic stress; Chlorophyll a fluorescence; climate change; Gas exchange; Oxidative stress; photosynthesis

Autumn fertilization with nitrogen improves nutritional status, cold hardiness and the oxidative stress response of Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) nursery seedlings - Andivia, Enrique; Márquez-García, Belén; VÁZQUEZ-PIQUÉ, JAVIER; Córdoba, Francisco; FERNÁNDEZ, MANUEL (Trees, 2011)
Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) is one of the most important species in forest communities of the western Mediterranean Basin, but is very vulnerable to environmental stress during the ﬁrst years of its life. In particular, summer drought and winter frosts limit the distribution, survival, and growth of Holm oak. These two stress factors can lead to plasmolysis and/or oxidative stress. We hypothesized that autumn fertilization with nitrogen (N) can improve plant tolerance to these abiotic stress factors and improve plant quality and therefore reforestation success. A 12-week autumn application of 30 or 60 mg N (plus 70 mg N applied to both treatments during the previous 28 weeks in the nursery, i.e. 100 and 130 mg N in total, respectively) improved overall growth, root growth capacity, frost tolerance, and nutritional status of plants relative to plants given 0.0 and 1.5 mg autumnal N, and had no negative effect on seedling response to water stress. A very small increment in N doses during the autumn (1.5 vs. 0.0 mg N) improved some morphological parameters, such as stem diameter (D) and shoot dry weight, and physiological parameters, such as total antioxidant activity. The highest autumnal N dose (60 mg) increased leaf nutrient content without decreasing the concentration, but had a tendency to reduce frost tolerance relative to seedlings given a lower autumnal N dose (30 mg).
Keywords: Frost tolerance; Holm oak; Mineral nutrients; Oxidative stress; water stress

Gas exchange and JIP-test parameters of two Mediterranean maquis species are affected by sea spray and ozone interaction - Mereu, Simone; Gerosa, Giacomo; Marzuoli, Riccardo; Fusaro, Lina; Salvatori, Elisabetta; Finco, Angelo; Spano, Donatella; Manes, Fausto (Environmental and Experimental Botany, 2011)
Mediterranean maquis coastal ecosystems are subject to multiple oxidative stresses of both natural and anthropic origin, as sea spray, drought, high irradiance and ozone. In this article it is hypothesized that the interaction of ozone and sea spray is additive as a consequence of a higher reactive oxigen species accumulation. To test the hypothesis, an experiment was conducted in an Open Top Chambers facility where plants of Quercus ilex L. and Arbutus unedo L. were exposed to two levels of ozone and two levels of sea spray. The response of the species was evaluated by measurements of structural parameters (shoot growth and leaf biomass) and physiological parameters (leaf level gas exchange and chlorophyll a ﬂuorescence). The results contradict the hypothesis as the interaction of the two stresses is antagonistic on both species. The structure of both species was negatively affected by sea spray, however the two stresses combined allowed a higher growth and leaf area in A. unedo. The leaf level physiology of A. unedo was only moderately affected by the two stresses alone and in combined, while that of Q. ilex was altered to a further extent by sea spray and by its combination with ozone: photosynthesis and efﬁciency of the PSII was reduced by sea spray while the ratio of PSII to PSI was increased; the two stresses combined, instead, decreased the PSII to PSI ratio allowing for a higher photosynthesis. It is concluded that A. unedo is more resistant than Q. ilex to the two stresses alone and in combination, that ozone and sea spray interact antagonistically, and that the activity of PSI has a key role in the stress response
Keywords: Antagonistic interaction; dark respiration; JIP-test; OTC; Oxidative stress; PSI

A 10-kDa class-CI sHsp protects E-coli from oxidative and high-temperature stress - Jofre, A; Molinas, M; Pla, M (PLANTA, 2003)
We report on a new cDNA clone (Qshsp10.4-CI) of a Quercus suber L. class-CI small heat-shock protein (sHsp) obtained from cork (phellem), a highly oxidatively stressed plant tissue. The deduced gene product lacks the C-terminal extension and the consensus I region of the alpha-crystallin domain, being the most C-terminally truncated sHsp reported to date. In an attempt to prove that a protective function is possible for such a truncated sHsp, we overexpressed in Escherichia coli three recombinant sHsp-CIs, one (rQsHsp10.4-CI) showing the same truncation as Qshsp10.4-CI, a second (rN49) lacking the whole alpha-crystallin domain, and a third (rN153) consisting of a full-length sHsp-CI. The overexpression of rN153 and, remarkably, rQsHsp10.4-CI but not rN49 enhanced cell viability under high temperature and, interestingly, under oxidative stress. These results show that the C-terminal extension and the consensus I region of the alpha-crystallin domain are dispensable, but amino acids 1-41 of the alpha-crystallin domain (including the consensus II region) are essential for the protective activity of sHsp-CIs. On the other hand, two-dimensional immunodetection patterns showed accumulation of ca. 10-kDa sHsp-CI immunorelated polypeptides in cork and other oxidatively stressed tissues but not in control and heat-stressed tissues. We discuss the possible role of highly truncated sHsps in relation to oxidative stress.
Keywords: chaperone activity; heat stress; Oxidative stress; Quercus; small heat-shock protein

Antioxidative systems, pigment and protein contents in leaves of adult mediterranean oak species (Quercus pubescens and Q. ilex) with lifetime exposure to elevated CO2 - Schwanz, P; Polle, A (New Phytologist, 1998)
The aim of the present study was to investigate the effects of elevated CO2 on the antioxidative systems and the contents of pigments, soluble protein and lipid peroxidation in leaves of adult oaks, Quercus pubescens and Quercus ilex, grown at naturally enriched CO2 concentrations. For this purpose, a field study was conducted at two CO2 springs in Central Italy. Measurements of the pre-dawn water potentials indicated less drought stress in trees close to CO2 springs than in those grown at ambient CO2 concentrations. Most leaf constituents investigated showed significant variability between sampling dates, species and sites. The foliar contents of protein and chlorophylls were not affected in trees grown close to the CO2 vents compared with those in ambient conditions. Increases in glutathione and other soluble thiols were observed, but these responses might have been caused by a low pollution of the vents with sulphurous gases. At CO2 vents, glutathione reductase was unaffected, and superoxide dismutase activity was significantly diminished, in both species. Generally, the activities of catalase, guaiacol peroxidase and ascorbate peroxidase as well as the sum of dehydroascorbate and ascorbate were decreased in leaves from trees grown in naturally CO2-enriched environments compared with those grown at ambient CO2 concentrations. The reduction in protective enzymes did not result in increased lipid peroxidation, but increased monodehydroascorbate radical reductase and dehydroascorbate reductase activities found in leaves of Q. pubescens suggest that the smaller pool of ascorbate was subjected to higher turnover rates. These data show that changes in leaf physiology persist, even after lifetime exposure to enhanced atmospheric CO2. The results suggest that the down-regulation of protective systems, which has also previously been found in young trees or seedlings under controlled exposure to elevated CO2 concentrations, might reflect a realistic response of antioxidative defences in mature trees in a future high-CO2 world.
Keywords: antioxidants; carbon dioxide enrichment; Drought; Oxidative stress; Quercus spp. (holm oak - white oak)